ChemInform Abstract: Insights Gained from Solvable Models into a Variety of Phase Transitions, Including Emergent Assemblies Plus Isoelectronic Series of Atomic Ions. Issue 8 (February 2015) - March, N. H.; Angilella, G. G. N.; Pucci, R.
Abstract Review: 44 refs.